A Matched Prospective Study of Human Immunodeficiency Virus Serostatus, Human Papillomavirus DNA, and Cervical Lesions Detected by Cytology and Colposcopy - L. O. Eckert; D. H. Watts; L. A. Koutsky; S. E. Hawes; C. E. Stevens; J. Kuypers; N. B. Kiviat (Hindawi Limited, 1999)
Objective: To compare the prevalence and type of human papillomavirus (HPV) infections in the genital tract of human-immunodeficiency-virus- (HIV) seropositive and -seronegative women matched for cytology and to examine prospectively the relationship of HPV DNA, colposcopic findings and cervical squamous intraepithelial lesions (SIL) in these matched seropositive and seronegative cohorts.